Le statut politique des petits territoires insulaires à vocation touristique a-t-il une influence sur leur performance économique et sociale ? Approche comparative - Louis Dupont (Études Caribéennes)
The development of small island economies depends on different variables, among them, the political status and tourism development. The purpose of the present study is to empirically isolate those determinants, particularly political status variable in order to investigate its influence on development process. Its point of departure is to compare 16 dependent with 19 independent islands in the Caribbean and Pacific across 25 socio-economic and demographic indicators. First, results indicate that political status is associated with two-thirds of the variation in development across the island sample. Second, dependent islands are much more affluent, socially advanced and demographically mature than their independent counterparts. However, those results should not be interpreted as arguments against decolonization, which is considered morally and broadly speaking sustainable. Third, there is some evidence that dependent islands with a high level of political autonomy are more affluent than status quo counterparts such as Guadeloupe and Martinique. This is why we are proposing for illustrative purposes a political governance model for the future of the two French Overseas Departments. The advantage of this study is to offer by data and empirical analysis, useful explanations in order to understand and adopt political reforms for islands which would have to choose a political governance model.